RE-OPENED SECTION OF THE DERBENT MUSLIM NECROPOLIS OF XITH-XIITH CENTURIES - Gadziev, Murtazali Serazutdinovic; Budajciev, Arsen Lahmanovic; Abdulaev, Abdula Magomedovic; Sausev, Kydyrali Bajramgazyevic (History, Archeology and Ethnography of the Caucasus, 2021)
As a result of archaeological observations in Derbent, carried out in 2020, a Muslim burial ground was discovered, representing a section of the medieval northern city necropolis, located behind the northern city defensive wall. More than 80 sarcophagus-like gravestones were discovered, made of a single stone monolith and consisting of an upper part - a body and a protruding rectangular plinth. They are of three main types: 1 - with a semicircular cross-section of the body (semi-cylindrical), 2 - with a lancet cross-section, 3 - with a rectangular cross-section of the body. There are sarcophagi nos. 1-3, two of which (sarcophagi nos. 1, 2) have figured images on the top of the case - this is an eight-pointed star or a simplified octogram - the famous Muslim symbol rubʿ al-Hizb or najmat al-Quds, associated with one of the main Muslim shrines - the Dome of the Rock (Masjid Qubbat as-Sahra) mosque in Jerusalem, but also known in the literature as the “Selçuklu Yıldızı” (Tur. Selçuklu Yıldızı), which became widespread in the Seljuk Empire in architectural decor and decorative and applied arts art ceramics, metal) in various variations. The length of the body of the identified sarcophagi ranges from 52 to 266 cm with a width of 19 to 68 cm and a height of 13 to 56 cm; the length of the plinth ranges from 68 cm to 288 cm with a width of 40-95 cm and a thickness of 5-10 cm. Obviously, the size of the sarcophagi reflects three age categories of the buried: children, adolescents, and adults. Sarcophagus No. 40 has an epitaph in Arabic in the Kufi script of the 11th-12th centuries. All in situ sarcophagi are oriented to the west and indicate the location of burials beneath them, apparently having the same orientation and made in elongated rectangular stone boxes (cysts). The revealed sarcophagi dating back to the last third of the 11th - 12th centuries. and their appearance in Derbent and Dagestan is associated with the Seljuk military-political and ethnocultural expansion in the Eastern Caucasus.